A comparative study of immersed boundary method and interpolated bounce-back scheme for no-slip boundary treatment in the lattice Boltzmann method: Part II, turbulent flows. (15th October 2019) - Peng, Cheng; Ayala, Orlando M.; Brändle de Motta, Jorge César; Wang, Lian-Ping
Highlights: No-slip boundary treatments are directly compared in two turbulent flows. Local turbulent statistics around solid interfaces are provided. IBM cannot predict dissipation rate correctly near solid interfaces. IBM has better robustness in suppressing acoustic noise in LBM. Abstract: In the first part of this study [1], we compared the performances of two categories of no-slip boundary treatments, i.e., the interpolated bounce-back schemes and the immersed boundary methods in a series of laminar flow simulations within the lattice Boltzmann method. In this second part, these boundary treatments are further compared in the simulations of turbulent flows with complex geometry to provide a next-level assessment of these schemes. Two non-trivial turbulent flow problems, a fully developed turbulent pipe flow at a low Reynolds number, and a decaying homogeneous isotropic turbulent flow laden with a large number of resolved spherical particles are considered. The major problem of the immersed boundary method revealed by the present study is its incapability in computing the local velocity gradients inside the diffused interface, which can result in significantly underestimated dissipation rate and viscous diffusion locally near the particle surfaces. Otherwise, both categories of the no-slip boundary treatments are able to provide accurate results for most of turbulent statistics in both the carrier and dispersed phases, provided that sufficient grid resolutions are used. The criteria of sufficient grid resolutions for each examined flow are also addressed in this document.